Motive Evidentiary in Premeditated Murder: Aligning the Norms and Practical - Rauzi, Fathur; Hadi, Muhammad Zaki Pahrul; Willems, Janou (Universitas Ahmad Dahlan, 2023)
Introduction to The Problem: Motive, if related to crime, refers to the urge contained in the mental attitude of the actor to implement that mens rea in an act that is committed to a crime actus reus. The incorporation of motive in cases involving premeditated murder under the legal framework of Article 340 of the Indonesian Criminal Code remains a contentious issue, lacking a consensus. While some individuals posit that premeditated murder necessitates the presence of a motive, contrasting viewpoints contend that the crime can be established without requiring evidence of a motive.Purpose: This study aims to provide an overview and analysis of the significance of understanding motives as a means for judges to find out the background of the premeditated murder so that the panel of judges renders a decision accurately and proportionately.Methodology: The method used in this research is the normative juridical approach that focuses on the study of literature and legislation with the specifications of analytical descriptive research.Findings: The study suggested that Article 340 of the Criminal Code lacks a comprehensive explanation of the presence of motives. Consequently, the implementation of motives is limited to the interpretation provided by legal scholars and the subjective discretion of the presiding judge in each individual instance. In the absence of an interpretation of this motive, the Panel of Judges is not obliged to find a motive for the murder. As a result, this leads to different decisions, some resulting in acquittal and others in conviction of the defendant, because the judge did not discover a motive for the murder during the presentation of evidence. Meanwhile, according to the Indonesian version of the Criminal Code, namely Law No. 1 of 2023, the existence of the motive is mandatory in sentencing as stated in Article 54 paragraph (11) sub b of the Criminal Code.Paper Type: Research Article